The molecular basis of beta thalassaemia in Bulgaria. Issue 10 (October 1989) - Kalaydjieva, L; Eigel, A; Horst, J
Abstract : Bulgaria is in a geographical area where beta thalassaemia is relatively common. The frequency of carriers is 2 to 3% of the population. Data on the molecular characteristics of the disorder were obtained from the study of 33 homozygous patients and 57 beta thalassaemia carriers. As in other Mediterranean ethnic groups, haplotype I and the splicing mutation in IVS-1 nt 110 are the most common. Haplotype V is second in frequency and is associated with three different mutations. The second most common mutation, beta null 39, is found in association with haplotype II in 80% of cases. A rare haplotype, possibly resulting from a crossover between a haplotype II and a haplotype V chromosome, was found in two thalassaemia carriers in association with frameshift 6. Altogether four mutations (IVS-1 nt 110, beta null 39, frameshift 6, and IVS-1 nt 6) account for 67% of the thalassaemia chromosomes. Their detection would permit direct fetal DNA analysis in 84% of the families studied (45% fully informative). RFLP analysis (haplotype plus AvaII psi beta) is 100% informative in 79% of the high risk families.